Biosynthesis of bimetallic and core–shell nanoparticles: their biomedical applications – a review. Issue 7 (21st June 2018) - Khatami, Mehrdad; Alijani, Hajar Q.; Sharifi, Iraj
Abstract : Recently, researchers succeeded in designing and manufacturing a new class of nanoparticles (NPs) called hybrid NPs. Among hybrid NPs, bimetallic and core–shell NPs were a revolutionary step in NPs science. A large number of green physiochemical and methods for nanostructures synthesis have been published. Eventually, physiochemical methods are either expensive or require the use of chemical compounds for the synthesis of bimetallic and core–shell nanostructures. The main challenges that scientists are facing are making the process cheaper, facile and eco‐friendly efficient synthesis process. Green synthesis (biosynthesis) refers to the use of bio‐resources (such as bacteria, fungi, plants or their derivatives) for the synthesis of nanostructures. The popularity of the green synthesis of nanostructures is due to their environmental friendliness and no usage of toxic materials, environmental friendliness for the synthesis or stability of nanostructure. Bimetallic and core–shell NPs have many biomedical applications such as removing heavy metals, parasitology, molecular and microbial sensor, gene carrier, single bacterial detection, oligonucleotide detection and so on. The purpose of this study is to discuss briefly the biosynthesised bimetallic and core–shell NPs, their biomedical applications.